2011
DOI: 10.1016/j.ophtha.2010.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes in the Ahmed Baerveldt Comparison Study after 1 Year of Follow-up

Abstract: Purpose To determine the relative efficacy and complications of the Ahmed FP7 Glaucoma Valve (AGV) and the Baerveldt 101–350 Glaucoma Implant (BGI) in refractory glaucoma. Design Multicenter randomized controlled clinical trial. Participants 276 patients, including 143 in the AGV group and 133 in the BGI group. Methods Patients aged 18–85 years with refractory glaucoma with intraocular pressure (IOP) greater than or equal to 18 mm Hg in whom an aqueous shunt was planned were randomized to undergo implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
210
4
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(252 citation statements)
references
References 24 publications
28
210
4
10
Order By: Relevance
“…The existing evidence seems to suggest that AGV might have a more favorable safety profile when compared to nonvalved GDIs [20,51,52,54,55,60,61,64]. On the other hand, non-valved GDIs seem to achieve lower pressures than the AGV [54,55,[57][58][59][62][63][64]. AGV is a useful surgical choice and represents a reasonable compromise between efficacy and potential surgery-related complications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The existing evidence seems to suggest that AGV might have a more favorable safety profile when compared to nonvalved GDIs [20,51,52,54,55,60,61,64]. On the other hand, non-valved GDIs seem to achieve lower pressures than the AGV [54,55,[57][58][59][62][63][64]. AGV is a useful surgical choice and represents a reasonable compromise between efficacy and potential surgery-related complications.…”
Section: Resultsmentioning
confidence: 99%
“…In the AGV group, IOP was reduced from 31.2 ± 11.2 mmHg at baseline to 15.4 ± 5.5 and 14.3 ± 4.7 mmHg at 1-year and 3-year follow-up, respectively [57,58]. In the Baerveldt group, IOP was reduced from 31.8 ± 12.5 mmHg at baseline to 13.2 ± 6.8 and 13.1 ± 4.5 mmHg at 1-year and 3-year follow-up, respectively [57,58]. At 5 years, after censoring for patients who underwent additional surgery or loss of light perception, IOP was reduced from 29.6 ± 10.1 at baseline to 14.7 ± 4.4 mmHg in the AGV group and from 28.3 ± 9.3 at baseline to 12.7 ± 4.5 mmHg in the Baerveldt group [59].…”
Section: Ahmed Glaucoma Valve Versus Baerveldt Implantmentioning
confidence: 86%
See 2 more Smart Citations
“…2,3 In vitro studies have shown a high variability of the opening and closing pressures needed to activate or deactivate the AGV, which may explain cases of hypotony after AGV implantation. 4 The present study aimed to assess whether intraoperative measurement of the opening and closing pressure can be used to identify individual valves with an increased risk of over-or underfiltration.…”
Section: Introductionmentioning
confidence: 99%